[Library Mantel - House "A"] - Julia Morgan::::::::: (1919)
A design drawing by Julia Morgan of "House A" during the construction of Hearst Castle. This drawing is labeled "Library Mantel - House A." The bottom right corner of the sketch is initialed "JMC".